2012
DOI: 10.1124/mol.111.077537
|View full text |Cite
|
Sign up to set email alerts
|

The Polyphenolic Ellagitannin Vescalagin Acts As a Preferential Catalytic Inhibitor of the α Isoform of Human DNA Topoisomerase II

Abstract: Polyphenolic ellagitannins are natural compounds that are often associated with the therapeutic activity of plant extracts used in traditional medicine. They display cancer-preventing activity in animal models by a mechanism that remains unclear. Potential targets have been proposed, including DNA topoisomerases II (Top2). Top2␣ and Top2␤, the two isoforms of the human Top2, play a crucial role in the regulation of replication, transcription, and chromosome segregation. They are the target of anticancer agents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 47 publications
3
16
0
Order By: Relevance
“…Whereas most catalytic inhibitors and poisons of human topo II act on both the a and b isoforms, a limited number of compounds have been described that preferentially inhibit one isoform (Gao et al, 1999;Toyoda et al, 2008;Auzanneau et al, 2012). To examine whether salicylate can inhibit the b isoform of topo II with equal potency, we performed decatenation assays utilizing purified topo IIa and topo IIb.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas most catalytic inhibitors and poisons of human topo II act on both the a and b isoforms, a limited number of compounds have been described that preferentially inhibit one isoform (Gao et al, 1999;Toyoda et al, 2008;Auzanneau et al, 2012). To examine whether salicylate can inhibit the b isoform of topo II with equal potency, we performed decatenation assays utilizing purified topo IIa and topo IIb.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has identified topo IIa-or topo IIb-specific poisons, with selectivity ranging from 1.5-fold to greater than 10-fold (Gao et al, 1999;Bandele and Osheroff, 2007;Toyoda et al, 2008). Recent work has reported the first isoform-selective catalytic inhibitors of topo IIa, polyphenolic ellagitannin derivatives (Auzanneau et al, 2012). The biochemical basis of isoform selectivity with these compounds and salicylate remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, davidiin, which was isolated from P. capitatum extract, was investigated as a potential anticancer ET with the ability of inhibiting cancer cell growth via downregulating the enhancer of zeste homolog 2 (EZH2) and inducing apoptosis as well as suppressing tumor growth in xenograft models of Bel7404 . Moreover, vescalagin was confirmed as a selective inhibitor of the α isoform of DNA topoisomerase II (Top2α) in human leukemic CCRF‐CEM cells, which indicated that vescalagin could inhibit DNA replication by suppressing Top2α‐mediated decatenation of kinetoplast DNA, and inhibit cancer cell proliferation with low systemic toxicity . ETs also played an important role of inhibiting NF‐κB pathway and angiogenesis in the inflammation pathway of prostate carcinogenesis in vitro .…”
Section: Anticancer Activities and Potential Mechanismsmentioning
confidence: 98%
“…ETs are bioactive polyphenols that are abundant in some fruit herbs such as fructus chebulae, Phyllanthus emblica , and Punica granatum L . In contrast to the rather limited distribution of GTs in nature, ETs are typical constituents of many plant families, with more than 500 natural products characterized so far, such as davidiin, tellimagrandin I/II, vescalagin, and so on. ETs have previously been shown to exhibit in vitro and in vivo anticancer properties such as cell‐cycle arrest and apoptosis induction against various cancer cell lines, including liver, estrogen‐responsive breast, leukemia, and colon cancer cells, as well as inhibition of tumor formation and growth in animals.…”
Section: Anticancer Activities and Potential Mechanismsmentioning
confidence: 99%
“…These highly hydroxylated compounds have well described powerful biological activities and can be classified according to their structure as phenolic acid derivates, flavonoids and tannins (Alberto et al 2011;Karou et al 2005). Concerning their antibacterial mechanism of action, it has been reported that polyphenols can interfere with nucleic acid synthesis (topoisomerase inhibition) (Auzanneau et al 2012;Lambert et al 2005), cytoplasmic membrane damage (perforation and/ or a reduction in membrane fluidity) (Ajuwon et al 2013), energy metabolism (NADH-cytochrome c reductase inhibition) (Moini et al 1999) and cell wall/membrane synthesis inhibition (Palacios et al 2014) reducing the bacteria colonization Lamb 2005, 2011). Moreover, the use of polyphenols in combination with other antimicrobial agents has also been cited as a successful practice to fight the drug resistance problem (Lin et al 2008;Rizzo et al 2014).…”
Section: Introductionmentioning
confidence: 99%